Response to Ustekinumab in a Patient with Severe Psoriasis when Adalimumab Dose Escalation Fails - Joaquín Borrás-Blasco,; Luisa Obon,; Isabel Hernández,; Dolores-Elvira Casterá,; Alejandro Gonzalez,; F. Javier Abad ,; J. Dolores Rosique-Robles, (Journal of Pharmacy and Nutrition Sciences, 2014)
Objectives: To report a case of response to ustekinumab in a patient with severe psoriasis when adalimumab dose escalation fail. Case Description: A 35-year-old Caucasian male was diagnosed as having psoriasis. He was started on methotrexate followed cyclosporine. Despite these treatments, the patient experienced an abrupt deterioration of his psoriasis [PASI 35]. The patient started treatment with adalimumab: initial dose of 80mg followed by 40mg in week 2. At week 3 he continued on adalimumab 40mg/two weeks with significant reduction of psoriasis. After 8 months of adalimumab therapy, he referred that adalimumab was effective only during the first week of treatment. The patient gave his written informed consent for adalimumab dose intensification. He started adalimumab 40mg/week, with an improvement of psoriasis. After 7 months of adalimumab dose intensification, the psoriasis worsened [PASI score =25 and CDLQI score 20]. We discontinued adalimumab and started therapy with ustekinumab, 45mg subcutaneously, was administered at weeks 0, 4 and every 12 weeks. The clinical response was impressive; at week 12 a PASI 90 response was achieved while the CDLQI score fell to the scale of 7. Efficacy was maintained after a 12 months of ustekinumab therapy. Conclusions: This case report provides valuable insight into the efficacy and tolerability of ustekinumab in a patient with severe psoriasis when adalimumab dose escalation fails. To our knowledge this is the first case published to date that describes the clinical efficacy of ustekinumab when adalimumab intensification dose escalation fails.